EXAMINING RELATIONSHIPS BETWEEN EFL STUDENTS' LEARNING STYLE, WRITING PROFICIENCY, AND SELF-ASSESSMENT - Suherman, Andri (ETERNAL (English, Teaching, Learning, and Research Journal), 2018)
This research article aimed to explore the relationship between students’ learning styles, writing proficiency, and self-assessment. The participants in this case study were forty Indonesian tertiary-level EFL learners. This study investigated language learning styles preferences of the participants, analyzed preferred language learning styles of the most proficient writers, and explored how the partcipants assess their writing ability. Multiple sources of data were collected, including questionnaires, self-assessment checklist, and students’ writings. The findings revealed three main points. First, based on the mean value and standard deviation, Communicative was the most popular learning styles among the students, followed by three others styles, called Concrete, Analytical, and Authority-Oriented. Second, based on the students’ writing scores, eight students were considered the most proficient writers, and most of them had applied Communicative learning style to help them organize their writings. Third, the most proficient writers, compared to the self-assessment performance of the least proficient writers, appeared to underestimate their writing ability. The pedagogical implications of this study were to provide insight to EFL teachers into how students’ learning styles can help them to make the necessary adaptation and changes in the instruction, and to inform EFL learners with some suggestions to carry out self-assessments to help them improve their writing performance.